Precipitation statistics from regional climate model at resolutions relevant for soil erosion - Fosser, Giorgia (Wissenschaftliche Berichte des Instituts für Meteorologie und Klimaforschung des Karlsruher Instituts für Technologie, 2014)
A major source of uncertainty in regional climate model simulations arises from the convection parameterisation. Increasing spatial resolution to the so-called convection-permitting scale allows switching off most of the convective parameterisations. Several studies prove the benefits of this spatial scale, but none of them is based on climatological time-scale (i.e. 30 years) as this research.